Gender Inequality and Education: A Content Analysis of Indonesian EFL Textbook - Luthfi Mahdya Susanti; Nunung Suryati; Utari Praba Astuti (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This study aims to discover the gender inequality in Indonesia EFL textbook and the author's perspective towards gender inequality found. This study is performed through descriptive qualitative. It was found that there is inequality of gender representations in four measuring variables. Males gain the higher amount of four representations in picture, written texts, name appearances, domestic roles, and variations of domestic roles activities. In addition, based on the interview result, it was found that there was no intention to put the gender inequality and stereotype. Stereotype found aimed to generate familiarity to make the learners easier to identify their surroundings.Abstrak: Penelitian ini bertujuan untuk mengetahui ketidaksetaraan gender dalam buku teks EFL Indonesia dan perspektif penulis terhadap ketimpangan gender yang ditemukan. Penelitian ini dilakukan secara deskriptif kualitatif. Ditemukan adanya ketidaksetaraan representasi gender dalam empat variabel pengukuran. Laki-laki memperoleh jumlah empat representasi yang lebih tinggi dalam gambar, teks tertulis, penampilan nama, peran domestlk, dan variasi aktivitas peran domestik Selain itu, berdasarkan hasil wawancara ditemukan bahwa tidak ada niat untuk menempatkan ketidaksetaraan dan stereotip gender. Stereotip yang ditemukan bertujuan untuk menimbulkan keakraban agar peserta didik lebih mudah mengidentifikasi lingkungannya.